The effects of a minimally invasive laser needle system on complete Freund's adjuvant-induced arthritis - Kang, Heesung; Son, Taeyoon; Lee, Aeju; Youn, Inchan; Seo, Dong Hyun; Kim, Han Sung; Jung, Byungjo (SPRINGER LONDON LTD, 2014)
The present study aimed to investigate the effects of a minimally invasive laser needle system (MILNS) on the acute progression of arthritis. Previous studies showed controversial clinical results regarding the effects of low-level laser therapy on arthritis, with the outcomes depending upon stimulation parameters such as laser wavelength and dosage. Based on the positive effects of MILNS on osteoporotic mice, we hypothesized that MILNS could potentially suppress the progression of arthritis owing to its biostimulation effects. Eight C57BL/6 mice with complete Freund's adjuvant (CFA)-induced arthritis were used as acute progression arthritis models and divided into the laser and control groups (n = 4 each). In the laser group, after minimally invasive laser stimulation, laser speckle contrast images (LSCIs) were obtained every 6 h for a total of 108 h. The LSCIs in the control group were obtained without laser stimulation. The effects of MILNS on the acute progression of arthritis were indirectly evaluated by calculating the paw area and the average laser speckle index (LSI) at the arthritis-induced area. Moreover, the macrophage population was estimated in the arthritis-induced area. Compared to the control group, the laser group showed (1) lower relative variations of the paw area, (2) lower average LSI in the arthritis-induced area, and (3) lower macrophage population in the arthritis-induced area. These results indicate that MILNS may suppress the acute progression of CFA-induced arthritis in mice and may thus be used as a potential treatment modality of arthritis in clinics.
Keywords: RHEUMATOID-ARTHRITIS; THERAPY; BONE; IRRADIATION; RATS; MICE